2019
DOI: 10.5861/ijrsp.2019.4004
|View full text |Cite
|
Sign up to set email alerts
|

Self-confidence and hardiness towards work readiness: Study on vocational high school students

Abstract: Work readiness is an essential factor needed by students to enter the workforce. This study aims to determine the effect of self-confidence and hardiness on students' work readiness. The population in this study were all students of Grade XII State Vocational High School 1 Seyegan, Sleman Yogyakarta. The sampling technique is cluster random sampling. The sample in this study consisted of 6 classes obtained randomly with 174 students in class XII. Data collection was conducted using several tools, namely the wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…This is in line with the study of Pulakos, Dorsey & White (2006), Polyhart & Bliese (2006), Huang et al (2014), andTentema et al (2019). Tentama et al (2019) revealed that two aspects of personality, namely self-confidence and hardiness, had a significant effect on the readiness to work for vocational school graduates. The occupation in the future require prospective workers who are accustomed to working under pressure, along with the rapidly changing work environment.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the study of Pulakos, Dorsey & White (2006), Polyhart & Bliese (2006), Huang et al (2014), andTentema et al (2019). Tentama et al (2019) revealed that two aspects of personality, namely self-confidence and hardiness, had a significant effect on the readiness to work for vocational school graduates. The occupation in the future require prospective workers who are accustomed to working under pressure, along with the rapidly changing work environment.…”
Section: Discussionmentioning
confidence: 99%
“…Makki et al (2015) study found a positive significant relationship between work readiness skills, career self-efficacy and career exploration among graduate students. Tentama et al (2019) found that the higher the student's confidence and hardiness, the better the work readiness. Schembari (2018) found that there was little or no relationship between anticipated person-job fit and the role of HEI in raising confidence.…”
Section: Concepts Models and Theories Addressing Confidence To Work I...mentioning
confidence: 98%
“…Work readiness consists of the industry-required competencies. Graduating from a VHS with a high level of job preparation will influence self-confidence at work, the capacity to get a career, and high levels of  ISSN: 2252-8822 production [13], [14]. In VHS, work readiness can be developed in phases through preparation, implementation, and evaluation of learning.…”
Section: Introductionmentioning
confidence: 99%